Tanzania at the Turn of the Century : Background Papers and Statistics - Government of the United Republic of Tanzania; World Bank (Washington, DC: World Bank, 2013)
This report is the successor to the Country Economic Memorandum for Tanzania prepared in 1996 (World Bank 1996). The 1996 memorandum focused on the challenge of reforms and paid particular attention to the impact of reforms on growth, incomes, and welfare in Tanzania. The present report draws out lessons from Tanzania's development experience of the past four decades, with emphasis on the period since the last report, and assesses the imperatives for higher sustained growth and better livelihood for its citizens in the future. The background papers presented in this Country Study review and assess Tanzania's actual growth and poverty reduction performance against its large natural potential and against countries at a comparable stage of development, analyze the main reasons behind the performance record, and then draw out the strategic and institutional imperatives for exploiting the country's vast potential for sustained growth and reduction of poverty in the long and medium term. The analysis focuses on development of the private sector and its increased role in scaling up overall growth and modernization of the Tanzanian economy. One chapter focuses on the Zanzibar economy and its development, even though Zanzibar is part of the union, because the policy and institutional framework for the island are distinct enough to merit separate attention. Also presented are the statistical appendices.